Relationship between thyroid-stimulating hormone, BDNF levels, and hippocampal volume in antipsychotic-naïve first-episode psychosis patients - Toll, Alba; Blanco-Hinojo, Laura; Berge, Daniel; Manzano, Ana; El Abidi, Khadija; Perez-Solà, Víctor; Mané, Anna (Frontiers in Psychiatry, 2023)
Introduction: Thyroid hormones play an essential role in hippocampus development, a key structure in psychosis. However, the role of these hormones in first episode psychosis (FEP) has received scant attention. It has been hypothesized that thyroid hormones could cause morphological modifications in the hippocampal structure through an up-regulation of BDNF. In this study, we sought to determine the relationship between thyroid-stimulating hormone (TSH) levels, peripheral BDNF levels, and hippocampal volume in antipsychotic-naïve FEP patients. A second aim was to determine whether TSH levels were associated with clinical symptomatology. Material and Methods: A total of 50 antipsychotic-naïve FEP patients were included in this study. At baseline, we collected fasting blood samples, registered sociodemographic and clinical variables (substance use, DUP, PANSS, GAF, and CDSS). Structural T1 MRI was performed at baseline to quantify brain volumes. No control group was used for this study. Results: Of the 50 patients, more than one-third (36%) presented alterations in TSH levels, mainly elevated levels (32% of patients). TSH levels were inversely correlated with both peripheral BDNF and hippocampal volume. On the multivariate analysis, the model that best predicted relative hippocampal volume was a single variable model (TSH levels). No significant association was observed between TSH level and clinical symptomatology. Discussion: These results suggest that thyroid hormones could have a neuroprotective effect on the hippocampus in FEP patients, possibly through their effect by? increasing BDNF concentrations, which could attenuate brain injury and neuroinflammation. Nevertheless, thyroid hormones could also affect hippocampal volume through other pathways.